Pengembangan Modul Elektronik Pembelajaran Karya Fiksi Berbasis Kearifan Lokal Bogor untuk Pembelajaran Sastra di Sekolah Menengah - Dinda Septiandari; Ratna Dewi Kartikasari (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
This research is motivated by the problems faced by students in understanding fictional texts. Many students struggle to connect literary content with their personal experiences or real-life contexts, resulting in low reading interest, poor comprehension, and limited participation in literature learning. To address this issue, this study aims to develop an electronic module on fictional works based on Bogor’s local wisdom, to be integrated into Indonesian language learning at the secondary school level. The module is designed using local folk stories from the Bogor region—such as legends, myths, and traditional tales—which are rich in cultural and moral values. This approach seeks to make literary material more relatable, contextual, and meaningful for students, thus enhancing their engagement and understanding. This research employs the Research and Development (R&D) method using the ADDIE model, which consists of five stages: 1) Analysis, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation. Data collection techniques include observation, interviews with teachers and students, expert validation (media, content, and language), and questionnaires to assess students’ responses to the developed module. The results indicate that the module received a very high level of validation from experts: 94.4% from media experts, 96.6% from content experts, and the Sundanese translation was reviewed and verified by language experts. Student responses during both initial and main trials showed that the module was categorized as highly feasible and effective. These findings demonstrate that the electronic module meets technical, pedagogical, and cultural standards. In conclusion, this study contributes to the development of culturally responsive teaching materials and offers an innovative and engaging alternative for literature instruction. It also supports students in deepening their appreciation for local culture while improving their ability to understand and analyze fictional texts more effectively.